Trade Unions and the Ex-Service Men, 1921 (1921)
1921 1918-1939 "Trade Unions and the Ex-Service Men, 1921" [T0131.jpg], 1921, Caledonian Press Ltd "Trade Unions and the Ex-Service Men" by Fred Bramley, Assistant Secretary of the TUC (1921). Bramley was General Secretary of the TUC 1923-1925. This pamphlet was written in response to criticisms made by the Government and the Press that the reintroduction of union rules and conditions for access to the workplace, suspended during World War I by the Treasury Agreement 1915, were obstructing the re-employment of ex-servicemen. The unions were accused of restricting access to skilled work by tight control over apprenticeships and by not supporting rehabilitation and retraining schemes for disabled workers.